KONTRIBUSI EKONOMI SYARIAH DALAM PEMBANGUNAN EKONOMI - Ahmad Hamdi; Sukandi Sukandi (Iltizam : Jurnal Ekonomi dan Keuangan Islam, 2025)
Islamic economics, based on Sharia principles, has rapidly developed in recent decades. However, there remains a gap in understanding its contribution to inclusive and equitable economic development. This study aims to explore the contribution of Islamic economics to a more equitable economic development and identify how Islamic economic instruments such as zakat, waqf, and sukuk can support this goal. The research method used is a literature study, analyzing relevant literature on Islamic economic theories and their implementation in economic development. The findings reveal that Islamic economics has significant potential in creating a more just and sustainable economic system. Instruments such as zakat, waqf, and sukuk have proven effective in supporting wealth redistribution and empowering communities. Islamic financial institutions also play a crucial role in improving financial inclusion and extending access to marginalized groups. This research concludes that the implementation of Islamic economics can contribute to a fairer, more sustainable, and inclusive economic development, although challenges in its implementation still exist. Therefore, collaboration among Islamic economic institutions, governments, and society is needed to maximize Islamic economics' contribution to global economic development.